YOLO trading: Riding with the herd during the GameStop episode - Štefan Lyócsa; Eduard Baumöhl; Tomáš Vŷrost (ZBW - Leibniz Information Centre for Economics, 2021)
We explore the 2020 and early 2021 price variation of four stocks: GameStop, AMC Entertainment Holdings, Blackberry and Nokia. The four stocks were subject to a decentralized short squeeze that exploited the short positions of institutional investors. This investor movement was likely initiated by retail investors concentrated mostly around the subreddit r/WallStreetBets (WSB). We demonstrate that part of the next day's price variation can be explained by an increase in activity on the WSB subreddit relative to Google searches (terms related to the event). We discuss implications for future research.
Keywords: G10; G17; C53; G24; 330; GameStop; WallStreetBets; Reddit; short squeeze; volatility